2013
DOI: 10.12659/msm.889432
|View full text |Cite
|
Sign up to set email alerts
|

Perception of transgenerational family relationships: Comparison of eating-disordered patients and their parents

Abstract: BackgroundDisturbances in various elements of transgenerational family functioning patterns are not uncommon in studies of eating disorders.We examined the relationship between patients’ perception of autonomy and intimacy in their families of origin and that of their parents in their own families of origin.Material/MethodsThe sample consisted of 112 girls who had a diagnosis of an eating disoder and their parents; 54 of the girls were diagnosed with anorexia nervosa restrictive subtype, 22 as anorexia nervosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
(42 reference statements)
1
8
0
2
Order By: Relevance
“…For instance, recent studies have found that poor maternal emotional regulation can lead to problems in family functioning due to distancing or excessive responsiveness. In particular, difficulties in maternal emotional regulation in families with adolescents could lead to increased risk for children in this particular stage of development [65,66]. Moreover, a recent study has pointed out that difficulties between parents and children involve negative psychological consequences for adolescents [43].…”
Section: A Possible Integrate Perspective For Understanding Eating DImentioning
confidence: 99%
“…For instance, recent studies have found that poor maternal emotional regulation can lead to problems in family functioning due to distancing or excessive responsiveness. In particular, difficulties in maternal emotional regulation in families with adolescents could lead to increased risk for children in this particular stage of development [65,66]. Moreover, a recent study has pointed out that difficulties between parents and children involve negative psychological consequences for adolescents [43].…”
Section: A Possible Integrate Perspective For Understanding Eating DImentioning
confidence: 99%
“…In addition, it was demonstrated that parents with psychopathology show maladaptive parental behaviors that mediate the development of psychopathology in children, especially in the adolescent period [ 27 ]. Many studies have focussed on the role of parental perception in the development of psychopathology in children, and it has been reported that parents of adolescents with eating disorders showed lower emotional participation and sensitivity and higher controlling and rejecting behavior [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…47 patients were diagnosed with restrictive anorexia (ANR), 16 with binge-purge anorexia (ANBP), 34 with bulimia nervosa (BUL), 15 patients were eligible for the ED-NOS category, 7 of whom had signs of subclinical restrictive anorexia (ANRS), 6 with subclinical binge-purge anorexia (ANBPS), and 2 with bulimia with subclinical characteristics (BULS). The DGN1 study results formed the basis for a number of publications describing the interactions between the occurrence of eating disorders and several psychosocial variables [15][16][17][18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%